The Urgency of Reading in the Character Formation of Generation Z Youth from an Al-Qur'an Perspective (Examination of Maudhu'i Tafsir) - Mukhammad Fatchur Rozi; Nyoko Adi Kuswoyo; Ahmad Zainuddin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research discusses the urgency of reading from generation Z of the perspective of the Koran and the implications of the character formed in it. Along with rapid technological development, generation Z faces major challenges in the form of literacy crises and moral decline. The phenomenon of low interest in reading among young people is associated with the negative influence of modernity and digital technology. In the context of the literacy crisis faced by young people in the digital era, this research raises the importance of reading as a fundamental character that can help generation Z to strengthen character and faith in facing the challenges of modern times. Using a maudhu'I interpretation approach, several verses of the Koran that will be analyzed include QS. Al-Alaq verses 1 and 3, QS. Al-Isra’ verse 14, QS. Al-Haqqah verse 19 which emphasizes the command to read and QS. Taha verse 114, QS. Yusuf verse 30, QS. Al-Kahf verses 13, 60, 62 and QS. Al-Anbiya’ verse 60 which shows the character of an ideal young man. This research aims to explore communication between the two classification verses. In order to provide solutions and understanding of how reading can form a strong and positive mentality both from a spiritual and social perspective in Generazi Z which is in line with the teachings of the Al-Qur’an.